Aspergillus section Fumigati – Epidemiological trends - A perspective from a National Reference Laboratory - Sabino, Raquel (2018)
Poster abstract publicado em: Mycoses. 2017;60(Suppl. S2):131-132. Disponível em:http://onlinelibrary.wiley.com/doi/10.1111/myc.12675/epdf